2021
DOI: 10.1051/e3sconf/202123400010
|View full text |Cite
|
Sign up to set email alerts
|

Environmental migration and country security: Theoretical analysis and empirical research

Abstract: The article considers the impact of environmental changes on population migration and security of countries. Theoretical aspects of Environmental migration, in particular its essence and types, are studied. The main directions of scientific research in this field are considered. In particular, much attention is about finding ways to adapt to changes in the environment and minimize the negative consequences of these changes to achieve sustainable development in both regions and countries. The study found that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Studies [4][5][6][7][8] have confirmed a casual relationships between the efficiency of the tourism sector, social, economic, and ecological development of a region. In [9,10], the authors argue that COVID-19 had a direct negative effect (increasing death rate) and also provoked a vast range of social and economic consequences, including a decline in tourism development.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Studies [4][5][6][7][8] have confirmed a casual relationships between the efficiency of the tourism sector, social, economic, and ecological development of a region. In [9,10], the authors argue that COVID-19 had a direct negative effect (increasing death rate) and also provoked a vast range of social and economic consequences, including a decline in tourism development.…”
Section: Literature Reviewmentioning
confidence: 92%
“…General theoretical issues of national security are revealed in the works of world scientists (Samusevych et al, 2021;Mentel et al, 2020;Kubaienko, 2018;Didenko et al, 2021;Didenko et al, 2020a). They reveal the concept of security, describe the category of national security, its types, components, indicators, methods of achieving state security, describe threatening factors, determinants, features of the shadow economy, threats of bureaucracy, corruption and other issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The environmental component is an integral part of sustainable development, the impact of which is greatly enhanced due to the extensive use of fossil resources and insufficient environmental protection. Uncontrolled pollution of territories can lead to economic consequences and negatively impact the environment [7,8], causing ecological disasters and migration of the working population [9,10]. At the same time, the Paris Agreement 2015 contains regulated requirements that disturb the transformation of energy balances in terms of reducing the share of coal [11,12] and expanding green energy production in the energy sector [13].…”
Section: Introductionmentioning
confidence: 99%